2023
DOI: 10.1080/10717544.2023.2173333
|View full text |Cite
|
Sign up to set email alerts
|

Development of an apolipoprotein E mimetic peptide–lipid conjugate for efficient brain delivery of liposomes

Abstract: Liposomes are versatile carriers that can encapsulate various drugs; however, for delivery to the brain, they must be modified with a targeting ligand or other modifications to provide blood–brain barrier (BBB) permeability, while avoiding rapid clearance by reticuloendothelial systems through polyethylene glycol (PEG) modification. BBB-penetrating peptides act as brain-targeting ligands. In this study, to achieve efficient brain delivery of liposomes, we screened the functionality of eight BBB-penetrating pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…On the other hand, an enhanced interaction with cell membrane structure is promoted by liposomes favoring the biological effect of the peptide. A strategy to encapsulate lipopeptides in liposome vesicles has been successfully adopted in other studies for the delivery of vaccines [ 32 ] or for the transport of drugs through the Brain–Blood Barrier [ 33 ]. Interestingly, as can be observed in Figure 3 and Figure 4 , plain liposomes (TLE and REV samples) were also shown to be able to induce collagen production, although with a less potent effect compared to the pal-KTTKS-loaded liposomes.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, an enhanced interaction with cell membrane structure is promoted by liposomes favoring the biological effect of the peptide. A strategy to encapsulate lipopeptides in liposome vesicles has been successfully adopted in other studies for the delivery of vaccines [ 32 ] or for the transport of drugs through the Brain–Blood Barrier [ 33 ]. Interestingly, as can be observed in Figure 3 and Figure 4 , plain liposomes (TLE and REV samples) were also shown to be able to induce collagen production, although with a less potent effect compared to the pal-KTTKS-loaded liposomes.…”
Section: Resultsmentioning
confidence: 99%
“…R8-RGD increased the cellular uptake 2-fold and nearly 30-fold compared to separate R8 and RGD, respectively, and in vivo studies in mice showed that R8-RGD-liposomes could be efficiently delivered into the brain and selectively accumulated in the glioma foci . Further examples showed that the functionalization with a peptide called ApoEdp (CFG­GGL­RKL­RKR­LLL­RKL­RKR­LL) yields 3.9-fold higher accumulation in the brain compared to the nonmodified liposome formulation …”
Section: Lipid-based Nanoparticles Functionalized With Cppsmentioning
confidence: 99%
“…53 Further examples showed that the functionalization with a peptide called ApoEdp (CFGGGLRKLRKRLLLRKLRKRLL) yields 3.9-fold higher accumulation in the brain compared to the nonmodified liposome formulation. 47 Uhl et al demonstrated that the modification of liposome surfaces with a cell-penetrating peptide (cyclic R9 peptide) allows mucosal permeation. Therefore the cyclic R9 (cR9) peptide was conjugated to a PEG12 linker containing a maleimide group, which was bound to a thiol-modified phospholipid to achieve a construct of lipid-PEG12-cR9.…”
Section: Surface-functionalized Liposomesmentioning
confidence: 99%
See 2 more Smart Citations